Analisis Pelaksanaan Ekstensifikasi Wajib Pajak Dalam Meningkatkan Penerimaan Pajak Penghasilan Orang Pribadi Pada KPP Pratama Jakarta Kembangan Tahun 2020-2021 - Siti Noviyanti; Jiwa Pribadi Agustianto; Raden Kusyeni (Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this study was to analyze the implementation of tax extensification, the obstacles to the implementation of tax extensification, and the efforts to overcome the obstacles to the implementation of tax extensification in increasing individual income tax revenue at Jakarta Kembangan Small Tax Office in 2020-2021. The research approach was a qualitative descriptive approach with data collection techniques in the form of interviews and observations. Based on the results of this study, the implementation of tax extensification carried out at Jakarta Kembangan Small Tax Office was in accordance with applicable regulations. The implementation of tax extensification in increasing individual income tax revenue was still not effective because new taxpayers from extensification decreased in 2021. Although the realization of payments from the results of extensification increased in 2020-2021, the realization of individual income tax revenue at Jakarta Kembangan Small Tax Office in 2021 did not reach the target with a relatively low percentage of only 39%. Taxpayers were difficult to find because the majority of Indonesians work in various informal ways, uncooperative taxpayers, and a lack of understanding of tax were the obstacles to implementing tax extensification. By conducting socialization and counseling to taxpayers, disseminating tax information massively, as well as observing and searching for data on potential Taxpayer transactions with related parties or agencies, could be efforts to overcome obstacles to the implementation of tax extensification.